2013
DOI: 10.4238/2013.january.16.8
|View full text |Cite
|
Sign up to set email alerts
|

Amplifiability of mitochondrial, microsatellite and amelogenin DNA loci from fecal samples of red brocket deer Mazama americana (Cetartiodactyla, Cervidae)

Abstract: ABSTRACT. We tried to amplify mitochondrial, microsatellite and amelogenin loci in DNA from fecal samples of a wild Mazama americana population. Fifty-two deer fecal samples were collected from a 600-ha seasonal semideciduous forest fragment in a subtropical region of Brazil (21°20ꞌS, 47°17ꞌW), with the help of a detection dog; then, stored in ethanol and georeferenced. Among these samples 16 were classified as "fresh" and 36 as "non-fresh". DNA was extracted using the QIAamp ® DNA Stool Mini Kit. Mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In order to avoid genotyping errors, several replicates should be extracted and compared [17][18][19]. In two studies using field-collected feces from mammals, one-third of the samples were successfully amplified [20,21]. Small mammals' hairs, when freshly collected (i.e., regularly visited hair traps), provided accurate genotyping and were as amplifiable and informative as liver samples [22].…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid genotyping errors, several replicates should be extracted and compared [17][18][19]. In two studies using field-collected feces from mammals, one-third of the samples were successfully amplified [20,21]. Small mammals' hairs, when freshly collected (i.e., regularly visited hair traps), provided accurate genotyping and were as amplifiable and informative as liver samples [22].…”
Section: Introductionmentioning
confidence: 99%
“…The amplification of at least one microsatellite locus in all the samples and 5-6 loci in ~70% of the samples analyzed indicated a high rate of success for fecal DNA. These results indicate that the use of fresh fecal samples can enhance the success of studies using fecal DNA samples ( Oliveira and Duarte, 2013 ). In contrast, based on samples collected in northern Chile during the summer, Espinosa et al (2015) concluded that fresh feces (based on the presence of mucus or deer observed defecating) and non-fresh feces (no mucus, deer not observed defecating) were equally efficient for successful DNA amplification in ungulate species.…”
Section: Discussionmentioning
confidence: 96%
“…Since some studies have shown that the success in amplification varies according to locus size ( e.g. Oliveira and Duarte, 2013 ), we also investigated the correlation between these variables by calculating Pearson's correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…For each scat found by the searching team, we transferred a 2-3 cm section to a DNA-free sample container (Sarstedt, Mawson Lakes, AUS) with 30 ml pure ethanol. Where mucus was still existent on the scat surface, it was sampled to increase the probability of successful DNA analyses (Oliveira and Duarte 2013). We stored samples protected from high temperatures and sunlight until further processing.…”
Section: Scat Detection Dogmentioning
confidence: 99%